ENVIRONMENTAL FACTORS REGULATE DEVELOPMENTAL RATE IN C. ELEGANS - Rashid, Sabih (My University, 2018)
Environmental factors, such as diet, can have a significant impact on the health of animals, influencing lifespan, development, and disease progression. The model organism Caenorhabditis elegans is a bacterivore whose development is characterized by an invariant pattern of cell division. This study investigated how C. elegans developmental rate is altered in response to 48 different bacterial diets. The bacterial species studied had a wide range of effects on developmental progression, with some bacteria dramatically decreasing developmental rate, while others caused developmental arrest in early larval stages. From these analyses, Staphylococcus species that caused very slow development of animals in the L1 stage were selected for further characterization. The slow developmental rate observed in these animals was rescued by supplementation with essential amino acids. Genetic analysis revealed that these effects were mediated through TOR signaling and were independent of insulin signaling. Loss of daf-15(raptor), a central component of TOR complex 1, inhibited the rescuing effects of the amino acid supplementation on developmental rate, suggesting that the slow development induced by Staphylococcus could be rescued by activating the TORC1 pathway. Autophagy, negatively regulated by TOR, is increased in worms fed Staphylococcus species, suggesting TOR activity is reduced, and supplementation through amino acids reduced autophagy. These data suggest that TOR signaling is reduced in C. elegans in response to certain bacterial diets, resulting in decreased developmental rate, and that this effect may be due to amino acid deficiency.
INVESTIGATING THE IMPACT OF BACTERIAL DIET ON DEVELOPMENTAL RATE IN THE MODEL ORGANISM CAENORHABDITIS ELEGANS
Keywords: C. elegans; amino acids; TOR; developmental rate; bacteria